Cross-linked thermoplastic elastomer composition, and production method thereof

JP2023142125A5Active Publication Date: 2025-03-04MITSUI CHEMICALS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022048831
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-24
Publication Date
2025-03-04
Estimated Expiration
2042-03-24

AI Technical Summary

Technical Problem

Existing crosslinked thermoplastic elastomers face issues with moldability, surface roughness, and the occurrence of eye stains due to viscosity differences and gelation during the manufacturing process, particularly when using organic peroxide and phenolic resin crosslinking agents.

Method used

A crosslinked thermoplastic elastomer composition is developed by simultaneously adding an organic peroxide and phenolic resin crosslinking agents to a mixture of ethylene/α-olefin/non-conjugated polyene copolymer and olefin polymer, followed by dynamic heat treatment to achieve uniform crosslinking, thereby improving moldability and suppressing eye stain formation.

Benefits of technology

The composition exhibits enhanced moldability, hardness, tensile strength, tensile elongation, and compression set, while effectively reducing eye stain occurrence, resulting in improved surface quality and processability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide a cross-linked thermoplastic elastomer composition having moldability, hardness, tensile strength, tensile elongation, and compression set that are necessary for practical use and having generation of die drool effectively suppressed, and to provide a production method thereof.SOLUTION: A cross-linked thermoplastic elastomer composition is subjected to dynamic cross-linking an uncross-linked composition containing (A) 100 pts.mass of an ethylene-α-olefin-nonconjugated polyene copolymer containing a constitutional unit derived from ethylene, a constitutional unit derived from a α-olefin of 3-20 carbons, and a constitutional unit derived from a nonconjugated polyene, (B) 30-75 pts.mass of an olefin-based polymer, (C) 0.5-1.5 pts.mass of an organic peroxide cross-linking agent, and (D) 1-5 pts.mass of a phenolic resin cross-linking agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a crosslinked thermoplastic elastomer composition and a method for producing the same.

Background Art

[0002] A composition obtained by mixing an olefin copolymer rubber with polypropylene is used as an olefin thermoplastic elastomer in fields such as automotive parts, household electric appliance parts, medical device parts, electric wires, and sundries. It is known that the performance such as compression set and oil resistance of an olefin thermoplastic elastomer is improved by adopting a crosslinked structure. As crosslinking agents for imparting such a crosslinked structure, sulfur crosslinking, peroxide crosslinking, phenol resin crosslinking, quinone dioxime crosslinking, etc. have been proposed.

[0003] An olefin thermoplastic elastomer having a crosslinked structure is obtained by subjecting a mixture of an olefin copolymer rubber-like substance and an olefin thermoplastic resin to dynamic heat treatment in the presence of a crosslinking agent. In the production process of a dynamically crosslinked thermoplastic elastomer, when an organic peroxide is used as the crosslinking agent, a large viscosity difference occurs between the crosslinked olefin copolymer rubber and the molecularly cleaved polypropylene resin, so that the dispersibility of the rubber component deteriorates and a coarse gel may be formed. Further, when this is extrusion-molded, the surface of the molded product becomes rough, the edge portion becomes rough, deposits of rubber components scraped off due to friction between the inner surface of the die and the rubber and rubber wear, called eye gloss, tend to appear, and an avatar-like appearance is seen on the surface of the molded product, resulting in problems such as lack of surface smoothness of the molded product.

[0004] A composition obtained by subjecting a mixture of an olefin copolymer rubber-like substance and an olefin thermoplastic resin to dynamic heat treatment with a phenol resin crosslinking agent exhibits the characteristic of low compression set, but has problems such as low fluidity and poor surface state of the molded product.

[0005] Patent Document 1 proposes an olefin-based thermoplastic elastomer that is pre-crosslinked with an organic peroxide and then subsequently crosslinked with a phenolic resin crosslinking agent.

[0006] Patent Document 2 proposes a method for producing an olefin-based thermoplastic elastomer by pre-crosslinking with a phenolic resin crosslinking agent, followed by crosslinking with an organic peroxide. This method is reported to produce a crosslinked thermoplastic elastomer with excellent compression set, strength, heat aging resistance, and fluidity, and with minimal generation of deposits.

[0007] Patent Document 3 also describes a composition for improving crosslinking efficiency, which includes an ethylene copolymer rubber, a crystalline olefin resin, and a crosslinking agent. [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Patent Publication No. 2004-137352 [Patent Document 2] Japanese Patent Publication No. 2014-24929 [Patent Document 3] Japanese Patent Publication No. 2005-36143 [Overview of the Initiative] [Problems that the invention aims to solve]

[0009] As a result of our investigation, we found that the cross-linked thermoplastic elastomers obtained from the aforementioned patent documents do not easily achieve the required moldability and appearance, and there is room for improvement.

[0010] Specifically, the olefin-based thermoplastic elastomer manufactured by the method described in Patent Document 1 has a problem of poor moldability, such as the formation of coarse gel due to the gelation of the rubber component, resulting in a rough surface on the extruded molded product. The cross-linked thermoplastic elastomer described in Patent Document 2 does not sufficiently suppress the generation of eye discharge. Patent Document 3 does not mention the suppression of eye discharge.

[0011] The present invention has been made in view of the above, and aims to provide a crosslinked thermoplastic elastomer composition and a method for producing the same that has the moldability, hardness, tensile strength, tensile elongation, and compression set necessary for practical use, while effectively suppressing the generation of deposits. [Means for solving the problem]

[0012] The present inventors have discovered that the above problems can be solved by a crosslinked thermoplastic elastomer composition obtained by dynamically crosslinking a mixture containing an ethylene-α-olefin-non-conjugated polyene copolymer and an olefin polymer, after simultaneously adding an organic peroxide crosslinking agent and a phenol resin crosslinking agent as crosslinking agents. This led to the completion of the present invention. Examples of embodiments of the present invention are shown below.

[0013] [1] (A) 100 parts by mass of an ethylene-α-olefin-non-conjugated polyene copolymer, comprising a constituent unit derived from ethylene, a constituent unit derived from an α-olefin having 3 to 20 carbon atoms, and a constituent unit derived from a non-conjugated polyene, (B) 30 to 75 parts by mass of olefin polymer, (C) 0.5 to 1.5 parts by mass of organic peroxide crosslinking agent, (D) 1 to 5 parts by mass of phenolic resin crosslinking agent A crosslinked thermoplastic elastomer composition obtained by dynamically crosslinking an uncrosslinked composition containing [a specific compound].

[0014] [2] The crosslinked thermoplastic elastomer composition according to item [1], wherein the olefin polymer (B) is at least one selected from a propylene polymer, an ethylene polymer, and a butene polymer.

[0015] [3] The crosslinked thermoplastic elastomer composition according to item [1] or [2], wherein the mass blending ratio of the organic peroxide crosslinking agent (C) to the phenol resin crosslinking agent (D) is 0.1 to 1.0.

[0016] [4] A cross-linked thermoplastic elastomer composition according to any one of items [1] to [3], further containing a softening agent (F).

[0017] [5] The crosslinked thermoplastic elastomer composition according to any one of items [1] to [4], wherein the uncrosslinked composition is a mixture containing the copolymer (A) and the olefin polymer (B), to which the organic peroxide crosslinking agent (C) and the phenol resin crosslinking agent (D) are simultaneously added.

[0018] [6] A molded article comprising a crosslinked thermoplastic elastomer composition as described in any one of items [1] to [5]. [7] Automotive component comprising a crosslinked thermoplastic elastomer composition as described in any one of items [1] to [5].

[0019] [8] A method for producing a crosslinked thermoplastic elastomer composition according to any one of items [1] to [5], (A) an ethylene-α-olefin-non-conjugated polyene copolymer containing constituent units derived from ethylene, constituent units derived from α-olefins having 3 to 20 carbon atoms, and constituent units derived from non-conjugated polyenes, and a mixture containing 30 to 75 parts by mass of (B) an olefin polymer per 100 parts by mass of the copolymer (A), A method for producing a crosslinked thermoplastic elastomer composition, comprising the step of dynamically heat-treating an uncrosslinked composition obtained by simultaneously adding (C) 0.5 to 1.5 parts by mass of an organic peroxide crosslinking agent and (D) 1 to 5 parts by mass of a phenol resin crosslinking agent to 100 parts by mass of the copolymer (A),

[0020] [9] The production method of the crosslinked thermoplastic elastomer composition according to item [8], wherein the mass blending ratio of the phenolic resin crosslinking agent (D) to the organic peroxide crosslinking agent (C) is 0.1 to 1.0.

Advantages of the Invention

[0021] According to the present invention, it is possible to provide a crosslinked thermoplastic elastomer composition having moldability, hardness, tensile strength, tensile elongation, and compression set necessary for practical use, and in which the generation of surface gloss is effectively suppressed, and a production method thereof.

Embodiments for Carrying Out the Invention

[0022] Hereinafter, the present invention will be described in detail. In this specification, a numerical range represented by "~" means a range including the numerical values described before and after "~" as the lower limit value and the upper limit value.

[0023] [Crosslinked Thermoplastic Elastomer Composition] The crosslinked thermoplastic elastomer composition of the present invention is obtained by dynamically crosslinking an uncrosslinked composition containing (A) an ethylene·α-olefin·non-conjugated polyene copolymer, (B) an olefin polymer, (C) an organic peroxide crosslinking agent, and (D) a phenolic resin crosslinking agent.

[0024] <(A) Ethylene·α-olefin·non-conjugated polyene copolymer> The ethylene·α-olefin·non-conjugated polyene copolymer (A) contains a structural unit derived from ethylene, a structural unit derived from an α-olefin having 3 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene.

[0025] Examples of α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-eicosene. Of these, α-olefins having 3 to 8 carbon atoms, such as propylene, 1-butene, 1-hexene, and 1-octene, are preferred, with propylene and 1-butene being particularly preferred, and propylene being the most preferred. That is, as the ethylene-α-olefin-non-conjugated polyene copolymer (A), ethylene-propylene-non-conjugated polyene copolymer and ethylene-1-butene-non-conjugated polyene copolymer are preferred, and ethylene-propylene-non-conjugated diene copolymer is the most preferred. Such α-olefins are preferred because the raw material costs are relatively low, copolymers (A) with excellent mechanical properties can be obtained, and molded articles with rubber elasticity can be obtained. The α-olefin may be used alone or in combination of two or more types.

[0026] Examples of non-conjugated polyenes include cyclic and linear non-conjugated polyenes. Examples of cyclic non-conjugated polyenes include 5-ethylidene-2-norbornene, dicyclopentadiene, 5-vinyl-2-norbornene, norbornadiene, and methyltetrahydroindene. Examples of linear non-conjugated polyenes include 1,4-hexadiene, 7-methyl-1,6-octadiene, 8-methyl-4-ethylidene-1,7-nonadiene, and 4-ethylidene-1,7-undecadiene. These non-conjugated polyenes may be used individually or in combination of two or more.

[0027] The ethylene-α-olefin-non-conjugated polyene copolymer (A) has a content of ethylene-derived components of 50-90 mol%, preferably 50-85 mol%, more preferably 50-75 mol%, relative to the total of ethylene-derived components, α-olefins with 3-20 carbon atoms, and non-conjugated polyene components, and a content of α-olefin-derived components of 9.5-49.5 mol%, preferably 14.5-49.5 mol%, more preferably 24.5-49.5 mol%, when the content is within the above range, the resulting cross-linked thermoplastic elastomer composition exhibits excellent mechanical strength.

[0028] The copolymerization amount of the non-conjugated polyene is preferably 1 to 40, more preferably 2 to 35, and even more preferably 3 to 30, in terms of iodine value. When the ethylene content in the ethylene-α-olefin-non-conjugated polyene copolymer (A) is low, for example, 50 to 75 mol%, the resulting cross-linked thermoplastic elastomer composition exhibits particularly good compression set at low temperatures.

[0029] The ethylene-α-olefin-non-conjugated polyene copolymer (A) preferably has a Mooney viscosity [ML1+4(100°C)] of 50 or higher, more preferably 50 to 350, at 100°C.

[0030] The ethylene-α-olefin-non-conjugated polyene copolymer (A) has an intrinsic viscosity [η] of preferably 0.8 to 4.0 dl / g, more preferably 1.0 to 3.5 dl / g, and even more preferably 1.1 to 3.0 dl / g, as measured in decalin (decahydronaphthalene) at 135°C.

[0031] Ethylene-α-olefin-non-conjugated polyene copolymer (A) can be used alone or in combination of two or more types.

[0032] The ethylene-α-olefin-non-conjugated polyene copolymer (A) may be a modified product obtained by graft copolymerization of an unsaturated carboxylic acid or its derivative, such as an acid anhydride.

[0033] The crosslinked thermoplastic elastomer composition preferably contains a crosslinked product formed by crosslinking at least a portion of component (A). When component (A) is crosslinked, it is possible to obtain a crosslinked thermoplastic elastomer composition that satisfies the hardness, tensile strength, tensile elongation, and compression set performance required for practical use.

[0034] <(B) Olefin polymers> The olefin polymer (B) may be a crystalline resin or an amorphous resin, but a crystalline resin is preferred.

[0035] Examples of the crystalline resin include homopolymers of α-olefins having 2 to 12 carbon atoms or copolymers with other α-olefins. This polymerization method may be either random polymerization or block polymerization. In the case of random copolymers, it is preferable that structural units derived from α-olefins, which are present in small amounts, are usually 40 mol% or less, preferably 30 mol% or less.

[0036] Examples of α-olefins having 2 to 12 carbon atoms include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, and 1-decene.

[0037] Preferred examples of olefin polymers include at least one selected from propylene polymers, ethylene polymers, and butene polymers. Here, a propylene polymer is a polymer whose main component is a structural unit derived from propylene, an ethylene polymer is a polymer whose main component is a structural unit derived from ethylene, and a butene polymer is a polymer whose main component is a structural unit derived from butene. Here, the main component refers to the component with the highest content ratio (mol%) among the structural units contained in the polymer. Specific examples of propylene polymers include propylene homopolymers and copolymers of propylene with one or more α-olefins having 2 to 12 carbon atoms. Specific examples of ethylene polymers include ethylene homopolymers and copolymers of ethylene with one or more α-olefins having 3 to 12 carbon atoms. Specific examples of butene polymers include 1-butene homopolymers and copolymers of 1-butene with one or more α-olefins having 2 to 12 carbon atoms.

[0038] In the case of a homopolymer, a propylene homopolymer is preferred. In the case of copolymers, the content of α-olefin copolymerized with ethylene, propylene, or 1-butene is preferably 1 to 30 mol%, more preferably 1 to 20 mol%. Among copolymers, propylene copolymers and butene copolymers are preferred, with propylene copolymers being more preferred. As for propylene copolymers, propylene copolymers called random copolymers or block copolymers are preferred.

[0039] Examples of the amorphous resin include ethylene-cyclic olefin copolymers. As the olefin polymer (B), one of the above polymers may be used alone, or two or more may be used in combination. For example, the olefin polymer (B) may be a propylene polymer, an ethylene polymer, or a butene polymer used alone, or a mixture may be used in which a propylene polymer, an ethylene polymer, or a butene polymer is the main component and other polymers are also included.

[0040] The melting point of the olefin polymer (B), measured according to the measurement method of JIS K 7121, is preferably 100 to 175°C, more preferably 120 to 170°C. When the melting point of the olefin polymer (B) is within the above range, the resulting crosslinked thermoplastic elastomer composition exhibits excellent heat resistance.

[0041] The melt flow rate (MFR) of the olefin polymer (B), measured at 230°C and under a 2.16 kg load according to the ASTM D-1238 measurement method, is preferably 0.01 to 50 g / 10 min, more preferably 0.1 to 30 g / 10 min, and even more preferably 0.3 to 20 g / 10 min. A MFR of the olefin polymer (B) within this range is preferable because it results in a crosslinked thermoplastic elastomer composition with excellent fluidity.

[0042] The content of the olefin polymer (B) in the aforementioned uncrosslinked composition is 30 to 75 parts by mass, preferably 40 to 70 parts by mass, and more preferably 40 to 65 parts by mass, per 100 parts by mass of ethylene-α-olefin-non-conjugated polyene copolymer (A).

[0043] <(C) Organic peroxide crosslinking agent> The organic peroxide crosslinking agent (C) can be either aromatic or aliphatic, and may be a single peroxide or a mixture of two or more peroxides. Specifically, di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyn-3, 1,3-bis(t-butylperoxyisopropyl) Examples include dialkyl peroxides such as butyl-peroxybenzene and 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane; peroxyesters such as t-butylperoxybenzoate, t-butylperoxyisopropyl monocarbonate, n-butyl-4,4-bis(t-butylperoxy)valerate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexine-3; and diacyl peroxides such as diacetyl peroxide, lauroyl peroxide, dibenzoyl peroxide, p-chlorobenzoyl peroxide, and 2,4-dichlorobenzoyl peroxide. Among these, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane and 1,3-bis(t-butylperoxyisopropyl)benzene are particularly preferred.

[0044] The organic peroxide crosslinking agent (C) preferably has a half-life temperature of 140°C to 230°C. Organic peroxides that satisfy this condition include dialkyl peroxides such as di-t-butyl peroxide, t-butylcumyl peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyn-3, 1,3-bis(t-butylperoxyisopropyl)benzene, and 1,1-di(t-hexylperoxy)-3,3,5-trimethylcyclohexane; t-butyl peroxybenzoate, t-butylperoxyisopropyl monocarbonate, n-butyl-4,4-bis(t-butylperoxy)valerate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexyn-3.

[0045] The content of the organic peroxide crosslinking agent (C) in the aforementioned uncrosslinked composition is 0.5 to 1.5 parts by mass, preferably 0.7 to 1.4 parts by mass, and more preferably 0.9 to 1.3 parts by mass, per 100 parts by mass of ethylene-α-olefin-non-conjugated polyene copolymer (A).

[0046] Along with organic peroxide crosslinking agents (C), crosslinking aids can also be used to ensure a homogenized crosslinking reaction. Specific examples of crosslinking aids include divinyl compounds such as divinylbenzene; oxime compounds such as p-quinone dioxime and p,p'-dibenzoylquinone dioxime; nitroso compounds such as N-methyl-N-4-dinitrosoaniline and nitrosobenzene; maleleimide compounds such as trimethylolpropane-N,N'-m-phenylenedimaleimide; and others such as sulfur, diphenylguanidine, and triallyl cyanurate. Other examples of crosslinking aids include polyfunctional methacrylate monomers such as ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, and allyl methacrylate; and polyfunctional vinyl monomers such as vinyl butyrate and vinyl stearate.

[0047] <(D) Phenolic resin crosslinking agent> The phenolic resin crosslinking agent (D) is a thermocrosslinkable phenolic resin. Examples of phenolic resin crosslinking agents include phenolic resins produced by the condensation of substituted or unsubstituted phenols with an aldehyde, preferably formaldehyde, or by the condensation of difunctional phenol dialcohols. Substituted phenols are preferably alkyl-substituted compounds having 1 to 10 carbon atoms. Halogenated phenolic resins can also be suitably used as the phenolic resin crosslinking agent (D).

[0048] For information on phenolic resin crosslinking agents, refer to U.S. Patents No. 3,287,440, No. 3,709,840, and No. 4,311,628.

[0049] As the phenolic resin crosslinking agent (D), commercially available phenolic resins can be appropriately selected and used. Examples of commercially available products that can be used as phenolic resin crosslinking agents (D) include Tackirol 201 (alkylphenol formaldehyde resin, manufactured by Taoka Chemical Industry Co., Ltd.), Tackirol 250-I (brominated alkylphenol formaldehyde resin with a bromination rate of 4%, manufactured by Taoka Chemical Industry Co., Ltd.), Tackirol 250-III (brominated alkylphenol formaldehyde resin, manufactured by Taoka Chemical Industry Co., Ltd.), PR-4507 (manufactured by Gun-ei Chemical Industry Co., Ltd.), Vulkaresat 510E (manufactured by Hoechst), Vulkaresat 532E (manufactured by Hoechst), Vulkaresen E (manufactured by Hoechst), Vulkaresen 105E (manufactured by Hoechst), Vulkaresen 130E (manufactured by Hoechst), Vulkaresol 315E (manufactured by Hoechst), and Amberol. Examples include ST 137X (manufactured by Rohm & Haas), Sumilight Resin PR-22193 (manufactured by Sumitomo Durez Co., Ltd.), Symphorm-C-100 (manufactured by Anchor Chem.), Symphorm-C-1001 (manufactured by Anchor Chem.), Tamanol 531 (manufactured by Arakawa Chemical Corporation), Schenectady SP1059 (manufactured by Schenectady Chem.), Schenectady SP1045 (manufactured by Schenectady Chem.), CRR-0803 (manufactured by UCC), Schenectady SP-1055 (manufactured by Schenectady Chem.), Schenectady SP-1056 (manufactured by Schenectady Chem.), CRM-0803 (manufactured by Showa Union Synthetic Co., Ltd.), and Vulkadu r A (manufactured by Bayer). Among these, brominated alkylphenol formaldehyde resin is preferred.

[0050] The phenolic resin crosslinking agent (D) is usually used together with an activator. Examples of activators include halogen donors such as stannous chloride, ferric chloride, chlorinated paraffin, chlorinated polyethylene, and chlorosulfonated polyethylene, and acid acceptors such as iron oxide, titanium oxide, magnesium oxide, silicon dioxide, and zinc oxide. If the phenolic resin crosslinking agent (D) is halogenated, a halogen donor may not be used.

[0051] The content of the phenol resin crosslinking agent (D) in the aforementioned uncrosslinked composition is 1.0 to 5.0 parts by mass, preferably 1.0 to 4.5 parts by mass, more preferably 1.5 to 4.0 parts by mass, and even more preferably 2.0 to 4.0 parts by mass, per 100 parts by mass of ethylene-α-olefin-non-conjugated polyene copolymer (A).

[0052] The amount of halogen donor added is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, per 100 parts by mass of ethylene-α-olefin-non-conjugated polyene copolymer (A). The amount of acid acceptor added is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, per 100 parts by mass of ethylene-α-olefin-non-conjugated polyene copolymer (A).

[0053] Furthermore, in the uncrosslinked composition, the mass blending ratio [(C) / (D)] of the organic peroxide crosslinking agent (C) to the phenol resin crosslinking agent (D) is preferably 0.10 to 1.0, more preferably 0.13 to 0.90, even more preferably 0.15 to 0.80, even more preferably 0.17 to 0.70, particularly preferably 0.20 to 0.60, and most preferably 0.23 to 0.50. By keeping the ratio of the organic peroxide crosslinking agent (C) to the phenol resin crosslinking agent (D) within the above range, the generation of eye discharge can be effectively suppressed in the method for producing the crosslinked thermoplastic elastomer composition described later.

[0054] <Other polymer components> The aforementioned uncrosslinked composition may further contain other polymer components other than the ethylene-α-olefin-non-conjugated polyene copolymer (A) and the olefin polymer (B). Examples of other polymer components include α-olefin polymer (E) (excluding the copolymer (A) and polymer (B) described above) and other elastomers.

[0055] α-olefin polymer (E) is, for example, a polymer of α-olefins having 2 to 20 carbon atoms (excluding copolymer (A) and polymer (B) described above), and includes homopolymers or copolymers of α-olefins having 2 to 20 carbon atoms.

[0056] Examples of α-olefins having 2 to 20 carbon atoms include linear α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene; and branched α-olefins such as isobutene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, 4,4-dimethyl-1-pentene, 4-methyl-1-hexene, 4,4-dimethyl-1-hexene, 4-ethyl-1-hexene, and 3-ethyl-1-hexene. Among these, α-olefins having 15 or fewer carbon atoms are preferred, and α-olefins having 10 or fewer carbon atoms are more preferred.

[0057] The α-olefin polymer (E) may further have constituent units derived from the other polymerizable compounds described above in copolymer (A), to the extent that it does not impair the objectives of the present invention.

[0058] In the α-olefin polymer (E), the content of constituent units derived from other polymerizable compounds is usually 10 mol% or less, preferably 5 mol% or less, and more preferably 3 mol% or less, out of 100 mol% of all constituent units constituting (E).

[0059] α-olefin polymers (E) specifically include low-density polyethylene, high-density polyethylene, ethylene-propylene random copolymer, ethylene-1-butene random copolymer, ethylene-propylene-1-butene random copolymer, ethylene-1-hexene random copolymer, ethylene-1-octene random copolymer, ethylene-propylene-ethylidene norbornene random copolymer, ethylene-propylene-1-butene-ethylidene norbornene random copolymer, and ethylene-1-butene-1-octene. Examples include ethylene copolymers such as random copolymers, propylene homopolymers, propylene copolymers such as propylene·1-butene random copolymers, propylene·1-hexene random copolymers, and propylene·1-octene random copolymers, butene copolymers such as 1-butene homopolymers, 1-butene·1-hexene random copolymers, and 1-butene·1-octene random copolymers, and 4-methyl-1-pentene copolymers such as 4-methyl-1-pentene homopolymers and 4-methyl-1-pentene·1-hexene copolymers. Among these, 4-methyl-1-pentene homopolymers and 4-methyl-1-pentene copolymers are preferred from the viewpoint of compatibility.

[0060] The intrinsic viscosity [η]E of the α-olefin polymer (E), measured in decalin at 135°C, is typically 0.1 to 10 dL / g, preferably 0.5 to 5 dL / g.

[0061] The melting point (Tm) of the α-olefin polymer (E), as measured by differential scanning calorimeter (DSC), is not particularly limited, but is preferably 60°C or higher, and more preferably 70 to 300°C, for reasons of heat resistance and strength.

[0062] The α-olefin polymer (E) can be produced by conventionally known methods, such as using a vanadium-based catalyst, a titanium-based catalyst, or a metallocene-based catalyst.

[0063] The aforementioned uncrosslinked composition may contain one or more α-olefin polymers (E).

[0064] The content of the α-olefin polymer (E) in the uncrosslinked composition is usually 50 parts by mass or less, preferably 40 parts by mass or less, based on 100 parts by mass of the total content of copolymer (A) and polymer (B).

[0065] <Other ingredients> The aforementioned uncrosslinked composition and crosslinked thermoplastic elastomer composition may further contain other components in addition to those described above, as long as they achieve the objectives of the present invention. Examples of other components include known additives commonly added to rubber, such as slip agents, antioxidants, ultraviolet absorbers, light stabilizers, conductivity imparters, antistatic agents, dispersants, flame retardants, antibacterial agents, neutralizing agents, softeners, fillers, colorants, and thermally conductive fillers.

[0066] The uncrosslinked composition preferably contains a softening agent (F) from the viewpoint of softening the resulting crosslinked thermoplastic elastomer composition, increasing its flexibility and elasticity, and improving the processability and fluidity of the uncrosslinked composition. Specific examples include mineral oil hydrocarbons such as paraffinic, naphthenic, and aromatic hydrocarbons, low molecular weight hydrocarbons such as polybutene and polybutadiene hydrocarbons, and glycerin, but among these, mineral oil hydrocarbons are preferred. Generally, mineral oil hydrocarbons are mixtures of aromatic hydrocarbons, naphthenic hydrocarbons, and paraffinic hydrocarbons. Those in which the proportion of carbon in aromatic hydrocarbons is 35% by weight or more of the total carbon content are called aromatic oils, those in which the proportion of carbon in naphthenic hydrocarbons is 30-45% by weight are called naphthenic oils, and those in which the proportion of carbon in paraffinic hydrocarbons is 50% by weight or more are called paraffinic oils. Of these, paraffinic oils are preferably used in the present invention. The softening agent may be used in a pre-mixed (oil-spread) form with component (A), or it may be used when preparing the uncrosslinked composition, or it may be added later when dynamically heat-treating each component to be incorporated into the uncrosslinked composition.

[0067] The melt flow rate (according to the measurement method of JIS K 7210, 230°C, 10 kg load) of the crosslinked thermoplastic elastomer composition of the present invention is typically 1 to 250 g / 10 min, preferably 5 to 200 g / 10 min, more preferably 5 to 180 g / 10 min, and even more preferably 10 to 150 g / 10 min, in order to obtain a composition with excellent moldability.

[0068] The crosslinked thermoplastic elastomer composition of the present invention is obtained by dynamically heat-treating the uncrosslinked composition. Specifically, the crosslinked thermoplastic elastomer composition of the present invention is produced by the method for producing the crosslinked thermoplastic elastomer composition described later. The crosslinked thermoplastic elastomer composition produced by the method for producing the crosslinked thermoplastic elastomer composition described later is a crosslinked body in which the generation of deposits during production is effectively suppressed, as described later, and which retains the hardness, tensile strength, tensile elongation, and compression set of an olefin-based thermoplastic elastomer.

[0069] [Molded body] The molded article of the present invention contains the crosslinked thermoplastic elastomer composition. Because the molded article of the present invention contains the crosslinked thermoplastic elastomer composition, the generation of deposits during manufacturing is effectively suppressed, and the hardness, tensile strength, tensile elongation, and compression set of the olefin-based thermoplastic elastomer are maintained. For this reason, the molded article of the present invention can be used in a variety of applications, and is suitably used, for example, in automotive components.

[0070] [Method for producing cross-linked thermoplastic elastomer compositions] The method for producing the crosslinked thermoplastic elastomer composition of the present invention is as follows: (A) an ethylene-α-olefin-non-conjugated polyene copolymer containing constituent units derived from ethylene, constituent units derived from α-olefins having 3 to 20 carbon atoms, and constituent units derived from non-conjugated polyenes, and a mixture containing 30 to 75 parts by mass of (B) an olefin polymer per 100 parts by mass of the copolymer (A), The process includes a step of dynamically heat-treating an uncrosslinked composition obtained by simultaneously adding (C) 0.5 to 1.5 parts by mass of an organic peroxide crosslinking agent and (D) 1 to 5 parts by mass of a phenol resin crosslinking agent to 100 parts by mass of the copolymer (A). By dynamically heat-treating as described above, crosslinking occurs, and a crosslinked thermoplastic elastomer composition, which is a crosslinked body, is obtained.

[0071] The components (A) to (D) used in the method for producing the crosslinked thermoplastic elastomer composition of the present invention are the same as the components (A) to (D) described in the uncrosslinked composition. Furthermore, the amounts of components (A) to (D) used in the method for producing the crosslinked thermoplastic elastomer composition of the present invention can be considered to be the same as the amounts of components (A) to (D) contained in the uncrosslinked composition. Components (E), (F), and other components that may be included in the thermoplastic elastomer composition can also be used as appropriate in the method for producing the crosslinked thermoplastic elastomer composition of the present invention. In the method for producing the crosslinked thermoplastic elastomer composition of the present invention, the uncrosslinked composition is prepared by adding an organic peroxide crosslinking agent (C) and a phenol resin crosslinking agent (D) to a mixture containing an ethylene-α-olefin-non-conjugated polyene copolymer (A) and an olefin polymer (B).

[0072] In the present invention, "dynamic heat treatment" refers to a process of melting and kneading a mixture containing the necessary components (the uncrosslinked composition) under shear force. As a method for dynamic heat treatment, it is preferable to knead using a kneading device capable of applying high shear force. Specifically, this can be done using a kneading device such as a mixing roll, an intensive mixer (e.g., a Banbury mixer, Brabender mixer, kneader, etc.), or a single-screw or twin-screw extruder. In particular, the use of a twin-screw extruder is preferred.

[0073] The present invention provides a method for producing a crosslinked thermoplastic elastomer composition, characterized by simultaneously adding an organic peroxide crosslinking agent (C) and a phenol resin crosslinking agent (D) to a mixture containing an ethylene-α-olefin-nonconjugated polyene copolymer (A) and an olefin polymer (B), and then dynamically heat-treating the mixture.

[0074] "Simultaneous addition" means that both the organic peroxide crosslinking agent (C) and the phenol resin crosslinking agent (D) are added at a time when the crosslinking reaction by either agent has not substantially occurred individually. In other words, "simultaneous addition" does not include cases where the organic peroxide crosslinking agent (C) is added after the crosslinking reaction by the phenol resin crosslinking agent (D) has started, or where the phenol resin crosslinking agent (D) is added after the crosslinking reaction by the organic peroxide crosslinking agent (C) has started. The fact that the crosslinking reaction by either the organic peroxide crosslinking agent (C) or the phenol resin crosslinking agent (D) has not started can be confirmed by the fact that the melt viscosity of the mixture has not substantially increased.

[0075] By adjusting the amounts of organic peroxide crosslinking agent (C) and phenol resin crosslinking agent (D) as described above, and further adjusting the timing of the addition of organic peroxide crosslinking agent (C) and phenol resin crosslinking agent (D) as described above, a crosslinked thermoplastic elastomer composition can be produced that effectively suppresses the generation of deposits without impairing the hardness, tensile strength, tensile elongation, and compression set of the olefin-based thermoplastic elastomer.

[0076] In the method for producing the crosslinked thermoplastic elastomer composition of the present invention, first, an ethylene-α-olefin-non-conjugated polyene copolymer (A) and an olefin polymer (B) may be mixed, and then an organic peroxide crosslinking agent (C) and a phenol resin crosslinking agent (D) may be added to the mixture and dynamically heat-treated. Alternatively, the ethylene-α-olefin-non-conjugated polyene copolymer (A), the olefin polymer (B), the organic peroxide crosslinking agent (C), and the phenol resin crosslinking agent (D) may be mixed together and dynamically heat-treated. Specifically, the ethylene-α-olefin-non-conjugated polyene copolymer (A) and the olefin polymer (B), along with any additional components used as needed, may be supplied to a kneading device and mixed, and then the organic peroxide crosslinking agent (C) and the phenol resin crosslinking agent (D) may be added. Alternatively, the ethylene-α-olefin-non-conjugated polyene copolymer (A), the olefin polymer (B), the organic peroxide crosslinking agent (C), and the phenol resin crosslinking agent (D), along with any additional components used as needed, may be supplied together to the kneading device. The method of supplying each component can be carried out in an appropriate manner depending on the equipment used.

[0077] The resin temperature during kneading in the dynamic heat treatment described above should be above the melting temperature of the olefin resin and 250°C or less, preferably 240°C or less, and more preferably 230°C or less. The set temperatures for the extruder cylinder should, for example, be 50 to 150°C at the beginning of the cylinder, 150 to 250°C at the end, and 180 to 250°C for the die.

[0078] When an organic peroxide crosslinking agent is used alone as a crosslinking agent, and a mixture of ethylene-α-olefin-non-conjugated polyene copolymer and an olefin polymer is subjected to dynamic thermal treatment, a crosslinking reaction occurs in the ethylene-α-olefin-non-conjugated polyene copolymer, causing an increase in viscosity in the rubber component, while a molecular cleavage reaction occurs in the olefin polymer, leading to an increase in melt flow rate, i.e., a decrease in viscosity. As a result, a large viscosity difference occurs between the crosslinked ethylene-α-olefin-non-conjugated polyene copolymer and the molecularly cleaved olefin polymer, which can lead to poor dispersibility of the crosslinked rubber component and the formation of a coarse gel even when high shear force is applied. Furthermore, when the resulting crosslinked material is extruded, the molded product may have a rough surface, rough edges, and be prone to discharge. In addition, when the resulting crosslinked material is injection molded, pitting is observed on the surface of the molded product, resulting in a poor surface condition.

[0079] It has been reported that when using phenolic resin crosslinking agents alone, high shear forces are required during kneading, which leads to high temperatures due to shear heating, causing discoloration that is thought to be caused by the phenolic resin crosslinking agent. As a result, the thermal stability is poor, and the resin composition turns brown.

[0080] In a method where a phenolic resin crosslinking agent is added after crosslinking with an organic peroxide crosslinking agent, molecular scleavage occurs in both the ethylene-α-olefin-unconjugated polyene copolymer and the olefin polymer, resulting in a large viscosity difference. Furthermore, if the crosslinking reaction with the phenolic resin occurs in an area with low dispersibility between the rubber and resin components, the rubber may gel, resulting in a coarse gel. When the resulting crosslinked material is extruded, the surface becomes rough, significantly reducing the commercial value of the molded product.

[0081] Patent Document 2 discloses a method in which a mixture of olefin copolymer rubber and olefin resin is crosslinked with a phenol resin crosslinking agent, followed by dynamic heat treatment in the presence of an organic peroxide crosslinking agent (d). This method has been reported to produce extruded products with excellent compression set, strength, heat aging resistance, and fluidity, as well as a clean surface condition without surface blemishes, and with minimal generation of pore deposits.

[0082] The method for producing the crosslinked thermoplastic elastomer composition of the present invention, by adjusting the amounts of the organic peroxide crosslinking agent (C) and the phenol resin crosslinking agent (D) as described above, and further adjusting the timing of the addition of the organic peroxide crosslinking agent (C) and the phenol resin crosslinking agent (D) as described above, can more effectively suppress the generation of deposits without impairing the hardness, tensile strength, tensile elongation, and compression set of the olefin-based thermoplastic elastomer compared to the conventional method described above. This effect will be specifically demonstrated in the examples described later. [Examples]

[0083] The present invention will be described in more detail below based on examples, but the present invention is not limited in any way to these examples. The materials used in the following examples and comparative examples, and the methods for evaluating each physical property, are as follows.

[0084] [Materials used] As the ethylene-α-olefin-nonconjugated polyene copolymer (A), the following (A-1) was used. (A-1): Ethylene-propylene-5-ethylidene-2-norbornene copolymer rubber (EPDM) [Ethylene content: 63% by mass, diene content: iodine value 13, Mooney viscosity ML1+4 (125℃) = 116, 40 parts by mass of the following softener (F) are spread in oil per 100 parts by mass of copolymer.]

[0085] The following (B-1) to (B-3) were used as olefin polymers (B). (B-1): Propylene copolymer (block copolymer of propylene and ethylene) [MFR (conditions: 230°C, 2.16 kgf): 9 g / 10 min, melting point measured by DSC: 162°C] (B-2): Propylene homopolymer [MFR (conditions: 230°C, 2.16 kgf): 12 g / 10 min, melting point measured by DSC: 165°C] (B-3): Propylene copolymer (random copolymer of propylene and ethylene) [MFR (conditions: 230°C, 2.16 kgf): 0.5 g / 10 min, melting point measured by DSC: 135°C]

[0086] The following (C-1) was used as the organic peroxide crosslinking agent (C). (C-1): Organic peroxide [2,5-dimethyl-2,5-di-(tert-butylperoxy)hexyn-3, perhexyn 25B, manufactured by Nippon Oil & Fats Co., Ltd.] Divinylbenzene DVB-810 (manufactured by Nippon Steel & Sumitomo Metal Chemical Co., Ltd.) was used as a crosslinking agent.

[0087] The following (D-1) was used as the phenolic resin crosslinking agent (D). (D-1): Brominated alkylphenol formaldehyde resin (product name: SP-1055F, manufactured by Schenectady) Zinc oxide (two types of zinc oxide, manufactured by Hakusui Tech Co., Ltd.) was used as the acid acceptor.

[0088] As a softening agent (F), a paraffin-based process oil (Diana Process Oil TMPW-100: manufactured by Idemitsu Kosan Co., Ltd.) was used.

[0089] [Example 1] The raw materials used were (A-1) 140 parts by mass (100 parts by mass as ethylene-α-olefin-non-conjugated polyene copolymer (A)); olefin polymer (B) 40 parts by mass (B-1), 6 parts by mass (B-2), and 7 parts by mass (B-3); organic peroxide crosslinking agent (C) 0.94 parts by mass (C-1), crosslinking aid 0.64 parts by mass, and softener (F) 0.94 parts by mass; phenol resin crosslinking agent (D) 2 parts by mass (D-1) and acid acceptor 0.14 parts by mass; and softener (F) 80 parts by mass as a post-added softener (120 parts by mass in total with the softener (F) contained in (A-1)).

[0090] The entire amount of the aforementioned raw materials was kneaded using an extruder (model number KTX-30, manufactured by Kobe Steel, Ltd., cylinder temperature: C1: 50℃, C2: 90℃, C3: 100℃, C4: 120℃, C5: 180℃, C6: 200℃, C7~C14: 200℃, die temperature: 200℃, screw rotation speed: 500 rpm, extrusion rate: 40 kg / h), followed by dynamic crosslinking to obtain crosslinked pellets.

[0091] Using a 100t electric automatic press (manufactured by Shoji Co., Ltd.), the crosslinked material pellets were press-molded at 230°C for 6 minutes, and then cooled and pressed at room temperature for 5 minutes to obtain a 2mm thick press sheet. A No. 3 dumbbell piece was punched out from the 2mm thick press sheet to prepare a 2mm thick test specimen.

[0092] The aforementioned cross-linked pellets, press sheets, and test specimens were used to perform the physical property measurements described later. The results are shown in Table 1.

[0093] [Examples 2-4, Comparative Examples 1-2 and 5] Crosslinked pellets were obtained in the same manner as in Example 1, except that the composition of each composition in Example 1 was changed as shown in Table 1, and 2 mm thick press sheets and test specimens were prepared.

[0094] The aforementioned cross-linked material pellets, press sheets, and test specimens were used to perform the physical property measurements described later. The results are shown in Table 1.

[0095] [Comparative Example 3] The raw materials used were 140 parts by mass of (A-1) as ethylene-α-olefin-non-conjugated polyene copolymer (A) (100 parts by mass as ethylene-α-olefin-non-conjugated polyene copolymer (A)); 40 parts by mass of (B-1), 6 parts by mass of (B-2), and 7 parts by mass of (B-3) as olefin polymers (B); 0.94 parts by mass of (C-1) as organic peroxide crosslinking agent (C), 0.64 parts by mass of crosslinking aid, and 0.94 parts by mass of softener (F); and 80 parts by mass of softener (F) as a post-added softener.

[0096] The entire amount of the aforementioned raw materials was kneaded and then dynamically crosslinked using an extruder (model number KTX-30, manufactured by Kobe Steel, Ltd., cylinder temperature: C1: 50℃, C2: 90℃, C3: 100℃, C4: 120℃, C5: 180℃, C6: 200℃, C7~C14: 200℃, die temperature: 200℃, screw rotation speed: 500 rpm, extrusion rate: 40 kg / h). Subsequently, 2 parts by mass of (D-1) as a phenolic resin crosslinking agent (D) and 0.14 parts by mass of an acid acceptor were added, and after kneading under the same conditions, dynamic crosslinking was performed to obtain crosslinked pellets.

[0097] Using the obtained crosslinked material pellets, a 2 mm thick press sheet and test specimens were prepared in the same manner as in Example 1. The crosslinked material pellets, press sheet, and test specimens were then subjected to the physical property measurements described later. The results are shown in Table 1.

[0098] [Comparative Example 4] The raw materials used were (A-1) 140 parts by mass of ethylene-α-olefin-non-conjugated polyene copolymer (A) (100 parts by mass of ethylene-α-olefin-non-conjugated polyene copolymer (A)); (B-1) 40 parts by mass, (B-2) 6 parts by mass, and (B-3) 7 parts by mass of olefin polymer (B); (D-1) 2 parts by mass and 0.14 parts by mass of acid acceptor as phenol resin crosslinking agent (D); and 80 parts by mass of softener (F).

[0099] The entire amount of the aforementioned raw materials was kneaded and then dynamically crosslinked using an extruder (model number KTX-30, manufactured by Kobe Steel Ltd., cylinder temperature: C1: 50℃, C2: 90℃, C3: 100℃, C4: 120℃, C5: 180℃, C6: 200℃, C7~C14: 200℃, die temperature: 200℃, screw rotation speed: 500 rpm, extrusion rate: 40 kg / h). Subsequently, 0.94 parts by mass of (C-1) as an organic peroxide crosslinking agent (C), 0.64 parts by mass of a crosslinking aid, and 0.94 parts by mass of a softening agent (F) were added, and after kneading under the same conditions, dynamic crosslinking was performed to obtain crosslinked pellets.

[0100] Using the obtained crosslinked material pellets, a 2 mm thick press sheet and test specimens were prepared in the same manner as in Example 1. The crosslinked material pellets, press sheet, and test specimens were then subjected to the physical property measurements described later. The results are shown in Table 1.

[0101] <Method for measuring physical properties> [Durometer A hardness (instantaneous value)] Using a press sheet, and in accordance with JIS K6253, a Type A measuring instrument was used to determine the A hardness by reading the scale immediately after contact with the indenter.

[0102] [Melt Flow Rate (MFR) and Moldability] Using a press sheet, the melt flow rate was measured at 230°C under a 10 kg load, in accordance with JIS K6721. The moldability was evaluated based on the measured MFR values ​​according to the following criteria. A: MFR is 5-200g / 10 minutes B: MFR is less than 5g / 10 min or greater than 200g / 10 min.

[0103] [Tensile properties] Using test specimens, the tensile breaking strength (TB) and tensile elongation at breaking (EB) were measured under the following conditions, in accordance with the method of JIS K6301. Measurement temperature: 23℃

[0104] [Compression Permanent Distortion (CS)] Press sheets were laminated in accordance with JIS K6250, and compression set tests were performed in accordance with JIS K6262. The test conditions involved using a laminated sheet with a thickness of 12 mm (six layers of 2 mm thick pieces), compressing it to 25% at 70°C for 22 hours, and measuring the compression set 30 minutes after the strain was removed (compressed).

[0105] [Flow Curve Swell] Using a press sheet, the flow curve swell (swell ratio) and viscosity were measured under the following conditions using a capillary rheometer "Capillograph 1D" (Toyo Seiki Seisakusho). 12 sec -1 The measured values ​​are shown in Table 1. Capillary tube: L=30 mm, D=1 mm, Inlet angle=180° Extrusion speed: 1, 2, 5, 10, 20, 50, 100, 200 mm / min (12 sec -1 ~2432sec -1 ) Measurement temperature: 200℃

[0106] [Eye discharge] The appearance of the die was checked after extruding the cross-linked pellets for 30 minutes using an extruder (model OSE-65, manufactured by Nagata Seisakusho Co., Ltd., cylinder temperature: C1: 170℃, C2: 180℃, C3: 190℃, C4: 200℃, C5: 200℃, C6: 200℃, C7: 200℃, C8: 200℃, die temperature: 200℃, screw rotation speed: 10 rpm). The evaluation was categorized as "A" if no eye discharge occurred after 30 minutes of driving, and "B" if eye discharge occurred. [Table 1]

Claims

1. (A) 100 parts by mass of an ethylene / α-olefin / non-conjugated polyene copolymer including a structural unit derived from ethylene, a structural unit derived from an α-olefin having 3 to 20 carbon atoms, and a structural unit derived from a non-conjugated polyene; (B) 30 to 75 parts by mass of an olefin polymer; (C) 0.5 to 1.5 parts by mass of an organic peroxide crosslinking agent; (D) 1 to 5 parts by mass of a phenolic resin crosslinking agent; A crosslinked thermoplastic elastomer composition obtained by dynamically crosslinking an uncrosslinked composition comprising the above compound.

2. 2. The crosslinkable thermoplastic elastomer composition according to claim 1, wherein the olefin polymer (B) is at least one selected from the group consisting of a propylene polymer, an ethylene polymer, and a butene polymer.

3. The crosslinked thermoplastic elastomer composition according to claim 1 or 2, wherein a mass blending ratio of the organic peroxide crosslinking agent (C) to the phenolic resin crosslinking agent (D) is 0.1 to 1.

0.

4. The crosslinkable thermoplastic elastomer composition according to any one of claims 1 to 3, further comprising a softener (F).

5. The crosslinked thermoplastic elastomer composition according to any one of claims 1 to 4, wherein the uncrosslinked composition is obtained by simultaneously adding the organic peroxide crosslinking agent (C) and the phenol resin crosslinking agent (D) to a mixture containing the copolymer (A) and the olefin-based polymer (B).

6. A molded article comprising the crosslinkable thermoplastic elastomer composition according to any one of claims 1 to 5.

7. An automobile part comprising the crosslinkable thermoplastic elastomer composition according to any one of claims 1 to 5.

8. A method for producing the crosslinked thermoplastic elastomer composition according to any one of claims 1 to 5, comprising the steps of: A mixture containing (A) an ethylene / α-olefin / non-conjugated polyene copolymer containing structural units derived from ethylene, structural units derived from an α-olefin having 3 to 20 carbon atoms, and structural units derived from a non-conjugated polyene, and (B) an olefin polymer in an amount of 30 to 75 parts by mass per 100 parts by mass of the copolymer (A), A method for producing a crosslinked thermoplastic elastomer composition, comprising a step of dynamically heat treating an uncrosslinked composition obtained by simultaneously adding 0.5 to 1.5 parts by mass of an organic peroxide crosslinking agent (C) and 1 to 5 parts by mass of a phenol resin crosslinking agent (D) to 100 parts by mass of the copolymer (A).

9. The method for producing a crosslinked thermoplastic elastomer composition according to claim 8, wherein a mass blending ratio of the organic peroxide crosslinking agent (C) to the phenolic resin crosslinking agent (D) is 0.1 to 1.0.